(untitled) (Carte Romanze, 2019)
The analysis is intended to propose a reading route within the narrative segments of Fresne by Marie de France. The aim is to point out the main rhetorical strategies adopted to codify the relationships between time and space as well as the building of binary symmetries and oppositions.